Stiffness Degradation Effects on Seismic Behavior of RC Frame Structures - Pham, Phu-Anh-Huy; Nguyen, Tan-Phat; Nguyen, Ngoc-Han (Civil Engineering Journal, 2026)
This study investigates the influence of stiffness degradation on the seismic performance of reinforced concrete (RC) frame structures, focusing on global response parameters including roof lateral displacement ratio (Δ/H), fundamental period (T1), and internal force redistribution. Nonlinear finite element analyses were conducted in SAP2000 for three representative RC frames (3-, 10-, and 20-story), considering beam-only, column-only, and combined stiffness degradation scenarios. The analytical framework integrates theoretical derivations of effective stiffness models with response-spectrum-based simulations, following the provisions of Vietnamese code (TCVN 9386:2012) and American code (ACI 318-25), as well as the formulations proposed by Paulay & Priestley, Elwood & Eberhard, and Tran & Li. The results reveal a clear height-dependent and nonlinear relationship between stiffness degradation and seismic response. In low-rise frames, beam stiffness reduction primarily governs lateral deformation, whereas column stiffness degradation dominates the dynamic behavior and internal force concentration in medium- and high-rise systems. When the effective stiffness ratio falls below EId/EIg = 0.5, roof drift and fundamental period increase sharply, and internal forces at the column base (M and Q) are amplified, leading to excessive deformation and potential instability. Among the models examined, the Tran & Li formulation provided the highest accuracy and stability when validated against experimental data. The findings emphasize that column stiffness should not be reduced below 50% of the gross section stiffness in high-rise frames to maintain acceptable vibration periods and control lateral drift. The novelty of this work lies in quantifying the nonlinear, height-dependent influence of stiffness degradation across multiple structural parameters, bridging the gap between component-level deterioration and system-level seismic performance. The results provide height-sensitive insights for improving nonlinear seismic analysis and performance-based design of RC frame buildings.